Financiamento da extensão no Instituto Federal da Paraíba no período de 2019 a 2022 - Oliveira, Maria Cleidenedia Morais (2024)
The research carried out at the IFPB campuses: Princesa Isabel, Catolé do Rocha, Cajazeiras, Cabedelo and Guarabira aimed to analyze the criteria adopted by management for funding extension activities from 2019 to 2022. The importance of these actions for the local community and the training of students was highlighted, underscoring the need to ensure stable and transparent financial resources to strengthen university extension. The objectives of the research were: a) a) To quantify the total budget resources allocated to Extension actions on the campuses under study from 2019 to 2022; b) To demonstrate the number of actions carried out in/by Extension in the same period; c) To present the criteria used by the campuses' management to finance Extension actions;d) To draw up a guiding document proposing pre-established criteria for funding IFPB Extension actions. The research methodology was based on bibliographical studies, analysis of official documents and semi-structured interviews with the managers of the Princesa Isabel, Catolé do Rocha, Cajazeiras, Cabedelo and Guarabira campuses. The data collected in the interviews with campus managers was essential for understanding the processes of financing extension. The qualitative-quantitative approach was adopted to analyze the data obtained and identify the budgetary resources allocated to extension actions in the period in question. During the period from 2019 to 2022, the results of the research pointed to disparities in the budget resources allocated to extension actions at the different IFPB campuses. The Cajazeiras Campus was identified as the one that invested the largest amount of resources in financing extension actions, followed by the Princesa Isabel Campus. Similarly, the Cajazeiras campus emerged as the leader, with the largest volume of extension actions carried out in the same period. These disparities can be attributed to the specific local needs of each region, areas of activity and priorities established by the management of each campus. In addition, there was a substantial reduction in budget resources for funding extension actions in 2020 and 2021, possibly due to the impact of the COVID-19 pandemic. These variations in resources have required adaptations in the extension actions on the campuses, demonstrating the importance of ensuring adequate and flexible financial resources to deal with adverse situations. Campus managers recognized the importance of extension as an integral part of the institutional mission, valuing its role in the comprehensive training of students and in strengthening the link between the campus and the community. Matching extension funding amounts with the results of the survey demonstrated recognition of the relevance of extension activities for institutional development and the well-being of the community surrounding the campus. In short, the research made an academic contribution by offering an in-depth analysis of extension funding at IFPB, identifying gaps, highlighting good practices and providing recommendations for strengthening and optimizing these initiatives. The social impact of extension activities was highlighted, promoting regional development and the integration of the Campus with the community, highlighting the transformative potential of these activities for society as a whole.